The Relationship Between Sunk Costs From The Perspective Of Young Players And Administrative Negotiation Among Youth Football Coaches (Category B) - M. M. Maytham Muzal Bahidh (Musamus Journal of Physical Education and Sport (MJPES), 2026)
Objectives. This study aimed to (1) identify sunk costs of Category (B) coaches from the perspective of young players, (2) identify administrative negotiation practices among Category (B) youth football coaches, and (3) examine the relationship between sunk costs and administrative negotiation. Materials and Methods. A descriptive correlational design was employed. The sample comprised 70 Category (B) football coaches from selected southern governorates, recruited through purposive sampling. Data were collected using two instruments: the Sunk Cost Fallacy Scale (25 items across 5 axes) and the Administrative Negotiation Scale (24 items across 4 axes). Results. Pearson correlation analysis showed a strong positive relationship between administrative negotiation and sunk cost fallacy (r = 0.832, p < 0.05). Conclusions. Strengthening administrative negotiation is associated with better management of sunk costs in youth football coaching contexts. Federations and clubs may reduce ineffective investment decisions by setting negotiation conditions and monitoring coaching outcomes systematically.